Efficacy of Mycoplasma hyopneumoniae vaccination before and at weaning against experimental challenge infection in pigs. Issue 1 (December 2016) - Arsenakis, Ioannis; Panzavolta, Luca; Michiels, Annelies; Del Pozo Sacristán, Rubén; Boyen, Filip; Haesebrouck, Freddy; Maes, Dominiek
Abstract Background Commercial bacterins are widely used at weaning to controlMycoplasma hyopneumoniae infections in pigs. However, it is not known whether the efficacy of vaccinating againstM. hyopneumoniae can be influenced by the weaning process when vaccination is applied at the day of weaning. The present study assessed the efficacy of a singleM. hyopneumoniae vaccination (Ingelvac MycoFLEX®) three days before weaning (V1) or at weaning (V2) against experimental challenge infection. Four weeks after vaccination, groups V1 and V2 (n = 20 pigs each) and a non-vaccinated, positive control group (PCG) (n = 20) were endotracheally inoculated with a virulentM. hyopneumoniae field strain. Five pigs were used as a negative control group. All pigs were euthanized 5 weeks after challenge. The main parameters investigated included macroscopic and histopathological lung lesions at necropsy, immunofluorescence (IF) staining and quantitative real-time PCR (qPCR) on broncho-alveolar lavage (BAL) fluid for quantifyingM. hyopneumoniae . Results The average macroscopic lung lesion scores in groups V1, V2 and PCG were 0.54, 0.88 and 1.04, respectively (P > 0.05). The average lymphohistiocytic infiltration scores in groups V1, V2 and PCG were 2.95, 3.16 and 3.61, respectively (P < 0.05). The average IF scores were: V1 = 1.13, V2 = 1.19 and PCG = 1.25 (P > 0.05), the qPCR values were: V1 = 102.94, V2 = 102.76 and PCG = 103.23 (P > 0.05). All pigs of the negative control group remained negative throughout the study. Conclusions Both vaccinated groups had lower numbers of macroscopic and histopathological lung lesions, and lower numbers ofM. hyopneumoniae organisms in the BAL fluid compared to the PCG. However, no firm conclusions could be made on whether weaning negatively influences the efficacy ofM. hyopneumoniae vaccination, since significant differences between the treatment groups were only obtained for the histopathological lung lesions. This could be attributed to the fact that milder macroscopic lung lesions were produced in the inoculated pigs, when compared to previous trials conducted by the same group. Further research under field conditions is warranted to assess possible differences between the two vaccination strategies.